course MTH 158 D|HۥÁassignment #014
......!!!!!!!!...................................
10:26:33 1.6.12 (was 1.6.6). Explain how you found the real solutions of the equation | 1 - 2 z | + 6 = 0.
......!!!!!!!!...................................
RESPONSE --> My book has the question as |1-2z| + 6 = 9, which makes sense because then subtracting the 6 from both sides would make the inequality equal to 3. However, without that |1-2z| + 6 being equal to nine, after subtracting the 6 from both sides, that makes |1-2z| = -6, and it's impossible to have a negative absolute value, so I am just completely confused. However, I'll try to solve it... |1-2z| = -6 will mean that 1 -2z = -6 or 1 -2z = 6 -2z = -6 or -2z = 5 -2z / -2 = -6 / -2 -2z / -2 = 5 / -2 z = 3 or z = - 5/2 {- 5/2, 3} confidence assessment: 1
.................................................
......!!!!!!!!...................................
10:28:03 ** Starting with | 1-2z| +6 = 9 we add -6 to both sides to get | 1 - 2z| = 3. We then use the fact that | a | = b means that a = b or a = -b: 1-2z=3 or 1-2z= -3 Solving both of these equations: -2z = 2 or -2z = -4 we get z= -1 or z = 2 We express our solution set as {-2/3,2} **
......!!!!!!!!...................................
RESPONSE --> So it was a typo... I thought so. Will I still have the consequence? self critique assessment: 1
.................................................
......!!!!!!!!...................................
10:40:12 1.6.30 (was 1.6.24). Explain how you found the real solutions of the equation | x^2 +3x - 2 | = 2
......!!!!!!!!...................................
RESPONSE --> x^2 + 3x - 2 = 2 or x^2 + 3x - 2 = -2 (x+4)(x-1) = 0 or x^2 + 3x = 0 ... x(x+3) = 0 x = {-4, 1} or x = {-3, 0} {-4, -3, 1, 0} confidence assessment: 2
.................................................
......!!!!!!!!...................................
10:40:29 ** My note here might be incorrect. If the equation is | x^2 +3x -2 | = 2 then we have x^2 + 3x - 2 = 2 or x^2 + 3x - 2 = -2. In the first case we get x^2 + 3x - 4 = 0, which factors into (x-1)(x+4) = 0 with solutions x = 1 and x = -4. In the second case we have x^2 + 3x = 0, which factors into x(x+3) = 0, with solutions x = 0 and x = -3. **
......!!!!!!!!...................................
RESPONSE --> ok self critique assessment: 2
.................................................
......!!!!!!!!...................................
10:43:54 1.6.36 (was 1.6.30). Explain how you found the real solutions of the inequality | x + 4 | + 3 < 5.
......!!!!!!!!...................................
RESPONSE --> | x + 4 | + 3 < 5 |x + 4| < 2 so x + 4 < 2 or x + 4 < -2 x < -2 or x < -6 confidence assessment: 2
.................................................
......!!!!!!!!...................................
10:47:07 STUDENT SOLUTION: | x+4| +3 < 5 | x+4 | < 2 -2 < x+4 < 2 -6 < x < -2
......!!!!!!!!...................................
RESPONSE --> I see. self critique assessment: 2
.................................................
......!!!!!!!!...................................
10:53:12 1.6.48 (was 1.6.42). Explain how you found the real solutions of the inequality | -x - 2 | >= 1.
......!!!!!!!!...................................
RESPONSE --> Using the rule |u| >= a is equivalent to u <= -a or u >= a -x-2 <= -1 or -x-2 >= 1 -x <= 1 or -x >= 3 x >= -1 or x <= -3 {x | x >= -1 or x <= -3} confidence assessment: 2
.................................................
......!!!!!!!!...................................
10:53:36 **Correct solution: | -x -2 | >= 1 Since | a | > b means a > b or a < -b (note the word 'or') we have -x-2 >= 1 or -x -2 <= -1. These inequalities are easily solved to get -x >= 3 or -x <= 1 or x <= -3 or x >= -1. So our solution is {-infinity, -3} U {-1, infinity}. **
......!!!!!!!!...................................
RESPONSE --> ok self critique assessment: 3
.................................................